Pendampingan Manajemen Resiko Petugas Panitia Pemungutan Suara (PPS) dan Kelompok Penyelenggara Pemungutan Suara (KPPS) Desa Bendosari, Kecamatan Kras, Kabupaten Kediri - Ali Syahidin Mubarok (GUYUB: Journal of Community Engagement, 2020)
The implementation of the 2020 regional elections during a pandemic Covid-19 has pros and cons. The two parties demanded certainty in the security of the implementation of various aspects, especially the safety and health of all participants in the regional elections. This study seeks to explain the impact of providing risk management training to PPS and KPPS officers. This research is a qualitative research with a case study approach. The number of participants in this study was 14 people. Data were collected by means of observation and interviews. The results showed that the provision of risk management training could increase the knowledge of PPS and KPPS officers regarding the risks that could arise during the election process. Risk management training is one way to equip PPS and KPPS officers in mitigating during the local elections. Massive training is required to provide an understanding of potential risks and an understanding of the main duties and functions of PPS and KPPS officers.